HDAC1 Silence Promotes Neuroprotective Effects of Human Umbilical Cord-Derived Mesenchymal Stem Cells in a Mouse Model of Traumatic Brain Injury via PI3K/AKT Pathway - Xu, Ling; Xing, Qu; Huang, Tuanjie; Zhou, Jiankang; Liu, Tengfei; Cui, Yuanbo; Cheng, Tian; Wang, Yaping; Zhou, Xinkui; Yang, Bo; Yang, Greta Luyuan; Zhang, Jiewen; et al. (Frontiers in Cellular Neuroscience, 2019)
Stem cell transplantation is a promising therapy for traumatic brain injury (TBI), but low efficiency of survival and differentiation of transplanted stem cells limits its clinical application. Histone deacetylase 1 (HDAC1) plays important roles in self-renewal of stem cells as well as the recovery of brain disorders. However, little is known about the effects of HDAC1 on the survival and efficacy of human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) in vivo. In this study, our results showed that HDAC1 silence promoted hUC-MSCs engraftment in the hippocampus and increased the neuroprotective effects of hUC-MSCs in TBI mouse model, which was accompanied by improved neurological function, enhanced neurogenesis, decreased neural apoptosis, and reduced oxidative stress in the hippocampus. Further mechanistic studies revealed that the expressions of phosphorylated PTEN (p-PTEN), phosphorylated Akt (p-Akt), and phosphorylated GSK-3β (p-GSK-3β) were upregulated. Intriguingly, the neuroprotective effects of hUC-MSCs with HDAC1 silence on behavioral performance of TBI mice was markedly attenuated by LY294002, an inhibitor of the PI3K/AKT pathway. Taken together, our findings suggest that hUC-MSCs transplantation with HDAC1 silence may provide a potential strategy for treating TBI in the future.